Biochemical and Enzymatic Changes in Apple Leaf Tissue during Autumnal Senescence - Spencer, Patricia W. (1972)
The biochemical changes occurring during the natural senescence of apple leaf tissue (Pyrus malus L., Golden Delicious) coincided with specific changes in the environment. Protein, sugars, and total nitrogen began declining in leaf tissue when the daylength first became less than 14 hours in the second week of August. The activity of triose phosphate dehydrogenase declined shortly afterwards, while the activities of malate dehydrogenase, glutamic dehydrogenase, and aspartate aminotransaminase increased. Chlorophyll, DNA, RNA, and fresh weight began declining when the daylength first became less than 12 hours at the end of September. At the same time sugars and the activities of RNase, polyphenol oxidase, and proteolytic enzymes began increasing. Protein synthesis, total nitrogen, and the activities of malate dehydrogenase, glutamic dehydrogenase, and aspartate aminotransaminase began declining rapidly and amino acids began to accumulate after the first frost of the year. RNase, polyphenol oxidase, and proteolytic activity reached their highest specific activities after the first frost.